PERAN PENGURUS PANTI ASUHAN INSAN PERMATA PEKANBARU DALAM MEMBENTUK KARAKTER MANDIRI - Astri Evianty Br. Manungkalit; Supentri Supentri; Indra Primahardani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the existence of several children who were born less fortunate like children in general, where they were abandoned by their parents when they were born (died) and some were forced to leave their parents due to a lack of economic life, so that with the presence of the board of directors as foster parents for children who play a role in every aspect of children's lives, especially in terms of forming independent characters in children from an early age. The purpose of this study was to find out how the role of the administrators of the Pekanbaru Insan Permata Orphanage in forming an independent character. This study uses qualitative methods and data collection techniques that researchers do are observation, interviews and documentation. Based on the results of the study, it can be concluded that the role of the administrators of the Pekanbaru Insan Permata Orphanage in forming an independent character has been carried out well, which can be seen from the efforts and efforts made by the orphanage to always try to guide, teach, instill religious values to God. The Almighty and strives for the best for the children, although there are still some obstacles faced by the administrators such as the differences in background when entering the orphanage, the character, age and culture that exist in each child at the Insan Permata Pekanbaru Orphanage so that it returns to each individual each child for everything he does, but still in the teachings and guidance of the administrator.Key Words: Role, Orphanage Manager, Independent Character.